QuickBooks 2010 - Biafore, Bonnie (Missing manual., 2010)
QuickBooks 2010 has impressive features, like financial and tax reporting, invoicing, payroll, time and mileage tracking, and online banking. So how do you avoid spending more time learning the software than using it? This Missing Manual takes you beyond QuickBooks' help resources: you not only learn how the program works, but why and when to use specific features. You also get basic accounting advice so that everything makes sense. QuickBooks can handle many of the financial tasks small companies face. QuickBooks 2010: The Missing Manual helps you handle QuickBooks with easy step-by-step instructions. Set up your QuickBooks files and preferences to fit your company Track inventory, control spending, run a payroll, and manage income Follow the money all the way from customer invoices to year-end tasks Export key snapshots in the convenient new Report Center Streamline your workflow with the new Online Banking Center Build and monitor budgets to keep your company financially fit Share information with your accountant quickly and easily QuickBooks 2010: The Missing Manual covers only QuickBooks 2010 for Windows.